A soro diferença para o HIV no contexto da conjugalidade - Silva, Neide Gravato da [UNIFESP] (2010)
The interface of the affective relations with the HIV infection involves sexual questions of the infection form, monogamy, relations between the sorts, expectations with the loving relation and the answers found for maintenance of the steady relationship, after the revelation of the HIV diagnosis in one of the partners The antiretroviral therapy brings a new hope to these couples, an improvement in life quality and a mortality reduction. The new techniques of post sexual exposition prophylaxis, the sperm laundering for couples who want to have children and the available medicines to reduce the vertical transmission, help to enlarge the set of offers to serum discordant couples. Therefore, the therapeutic adverse effects may difficult the marriage convivence, the lipodistrophy, the erectile dysfunction disturbing the sexual relationship, the depression charts, diabetics and the lipodispidemy, forcing the changing of habits in the couple quotidian. The serum difference question hands different aspects, in the biologic point of view, it is not possible to accurate preview the exact moment when the transmission by sexual way may occur, though high vulnerability situations have been observed in which the infection doesn’t occur due to the kind of relation, level of infection capacity of the infected partner In the subjective point of view many situations can derivate from that relation transforming in a factor of conflict in the relationship, but different are the couples perceptions by the part of the HIV hander as well by its non infected partner. It is necessary that the health services discuss this demand, to facilitate the shelter of the negative partner, bringing him to this discussion with the sick person or virus holder, reducing his exposition and the increase of the epidemic cases, granting access to technologies to find ways of improving the life quality and reducing these couples vulnerability.